Estimate wind speed in Ninewa province using Weppel parameters - Al Rajbo, Waleed Asmair; Hamam, Faten Mohammed (Journal of natural sciences, life and applied sciences, 2017)
The study and forecasting of wind speed is of great importance in weather phenomena, climate and wind energy investment for electricity and other uses. The aim of this paper is to estimate the mean monthly values of wind speed in five Meteorological stations in Ninava Governorate (Mosul, Rabea ,Sin jar ,Talafar ,Baag) using weibull parameter . The estimated mean monthly values of wind speed using weibull parameters in all stations are nearly equal to the measured values. The coefficient of determination (R2 ) between the measured and estimated values in all stations are (0.997, 0.956, 0.995, 0.997, 0.994) . R2 between the measured and estimated values of wind speed in the whole Ninava Governorate is gives a very high value equal to ( 0.998) . This mean that the model is very accurate.